Strategic Business Plan Development for Griya Khazna Muslim Fashion Store - Ramdhani, Haidar Zahran; Arimbawa, Putu Adi Putra (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to formulate a comprehensive business plan for Toko Griya Khazna, a Muslim fashion retailer operating through both offline and online channels, to adapt to changing market trends and strengthen business competitiveness in the digital era. Design/Methodology/Approach – This study employs a qualitative descriptive approach. Data were collected through in-depth interviews, participatory observations, and documentation. The data were analyzed using strategic and business analysis tools, including SWOT analysis, Porter’s Five Forces, Marketing Mix 4P, and financial ratio analysis to evaluate business conditions and develop appropriate strategies. Findings – The results indicate that Toko Griya Khazna has significant growth potential due to its broad target market, strong value proposition, and effective use of digital marketing channels. Financial projections show positive cash flow, healthy profitability, and strong liquidity and solvency ratios, indicating that the proposed business development strategy is feasible and sustainable. Originality/Value This research provides value by integrating a data-driven stock management system with adaptive marketing strategies, offering a comprehensive business plan that strengthens competitiveness in the Muslim fashion segment and serves as a practical model for similar SMEs seeking sustainable growth.